Inventory management system using RFID for FSKKP laboratory in UMP - Jessica Olivia @ Simon Paie, Anak Paie (2011)
To the success of my final year project, I would like to thank first of all my honorable supervisor of this project Dr.Norrozila binti Sulaiman who have guide me along the whole development process.She has contributed towards my understanding and thoughts about what this is all about.Grateful thanks too to my beloved dad (Simon Paie)mum(Theresa Mary Pereira,Konstantinos,Nor Haslizah, Noor Izzarria Aslinie,Nurul Azurin,Nurul Nadia Suhaida and other fellow postgraduates students that is not mentioned in this limited space who have given me the full support, advices and providing their assistance in supplying useful information when needed to continue doing and never giving up hope from the difficulties that I faced.Their view and tips are very much useful indeed.